Early career psychiatrists in Europe during the COVID-19 pandemic: a cross-sectional study - Pinto da Costa, Mariana; Kilic, Ozge; Chumakov, Egor; Seker, Asilay; Sampogna, Gaia; Kazakova, Olga; Ismayilova, Jamila; Mogren, Tove; Mucci, Federico; Naesström, Matilda; Baessler, Franziska; Gargot, Thomas; et al. (CNS spectrums, 2025)
Objective: We aimed to investigate the effects of the COVID-19 pandemic on the education and professional development, working conditions, and wellbeing of early career psychiatrists (ECPs) in Europe, as well as their attitudes to telepsychiatry. Methods: A questionnaire comprising 24 items was designed by the Early Career Psychiatrists Committee of the European Psychiatric Association. Data were collected online from June 2020 to September 2021. A series of multiple regression analyses were conducted to determine variables that could predict the dependent variables. Results: Data were obtained from 517 early career psychiatrists from 39 different countries. Men were more confident than women in their knowledge of COVID-19 symptoms and management, including in managing patients with a comorbidity of COVID-19 and a mental disorder. Providing specific recommendations during the COVID-19 pandemic, access to additional educational activities for ECPs, following COVID-19-related recommendations and access to protective equipment were the significant predictors of a higher confidence in managing patients with comorbidity of COVID-19 and mental disorders. The obligation to change the place of work predicted a decreased satisfaction with telepsychiatry as well as a decreased willingness to use telepsychiatry after the COVID-19 pandemic, while a diagnosis of COVID-19, having recommendations for telepsychiatry and access to dedicated platform for telemedicine were predictors of an increased satisfaction with telepsychiatry. Conclusions: The COVID-19 pandemic has affected ECPs in Europe to varying degrees. The results point to areas where decision-makers can improve the working conditions for ECPs.
Veröffentlicht: 21. November 2025
Gesehen am 19.02.2026